Species authentication methods in foods and feeds: The present, past, and future of halal forensics - Md. Eaqub, Ali; Muhammad, Kashif; Md. Kamal, Uddin; Uda, Hashim, Prof. Dr.; Shuhaimi, Mustafa, Prof. Madya Dr.; Yaacob, Che Man, Prof. Datuk Dr. (Springer Science+Business Media, LLC., 2013)
Link to publisher's homepage at http://link.springer.com/